Freeway Space Measurement by Willis Gauge and Sprung Divider (Medical Forum Monthly, 2024)
Objective: To compare the accuracy of Willis gauge and Sprung divider in determination of freeway space in dentate subjects.Study Design: cross-sectional comparative study.Place and Duration of Study: This study was carried out at Department of Prosthodontics, Lahore Medical and Dental College, Lahore from March 2010 to August 2010.Materials and Methods: Three hundred dentate subjects were included in this study. Both Willis gauge and Sprung divider methods were performed on same subject to measure the freeway space. Subjects were seated in comfortable upright position with unsupported head. Freeway space was measured by both Willis gauge and Sprung divider. The difference between the two measurements of rest position and maximum intercuspation was taken as freeway space. The collected data was entered in proforma. SPSS version 17 was used to analyze the data. Mean and SD was taken for age and gender. The measurement of both methods were compared through chi square test p value < 0.05 was considered significant.Results: Out of 300 subjects, freeway space was achieved 217 (72.33%) with Willis Gauge and in 247 (82.33%) subjects freeway space was achieved with Sprung Divider. Although the achievement rate was slightly high with Sprig Divider as compare to Willis gauge method but it was non-significant (p-value = 0.078).Conclusion: Sprung Divider measurement of freeway space is somewhat superior to Willis gauge.